TUFIA IN CHINUA ACHEBE’S THINGS FALL APART AND IN HORACE WALPOLE’S THE CASTLE OF OTRANTO - Abu Fanani (STKIP PGRI Jombang, 2017)
In this article, the researcher analyzes Tufia in Chinua Achebe‘s Things Fall Apartand in Horace Walpole‘s the Castle of Otranto. The researcher then uses descriptive and dramatic method in analyzing the two novels through characterization by which the researcher means to present the characters mainly through description and discussion as well as through reporting the character‘s speech and action. At last, the researcher draws conclusion that the main characters, Okonkwo and Manfred undergo a tufia/a curse in the end of the story.